ANALISIS LITERASI DIGITAL MAHASISWA CALON GURU MELALUI PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS KONTEN SAINS DIGITAL - Saputra, Aji; Andy Hermawan; Hilya Wildana Sofia (JEAS (Journal of Educational and Applied Science), 2024)
This research aims to determine students' digital literacy abilities after implementing learning using PjBL model based on Digital Science Content. The method used in this research is quantitative descriptive. This research was carried out at the Faculty of Teacher Training and Education, Khairun University. The selection of respondents used a saturated sampling technique with a total of 32 students taking the Basic Concepts of Physical Science course. The data sources in this research are primary data obtained from respondents and secondary data obtained from literature that supports the research results. Data collection techniques were carried out through observation, questionnaires and literature study. The results of this research show that good digital literacy has been achieved with an average percentage of 85.15% after implementing the PjBL model based on digital science content. There are 6 indicators that show excellent results, namely: accessing, understanding, evaluating, distributing, producing and participating. There are 3 indicators that show good results, namely: selecting, verifying and collaborating. There is 1 indicator that shows poor results, namely: analysis.